A Metagenomic Insight Into the Hindgut Microbiota and Their Metabolites for Dairy Goats Fed Different Rumen Degradable Starch - Han, Xiaoying; Lei, Xinjian; Yang, Xuexin; Shen, Jing; Zheng, Lixin; Jin, Chunjia; Cao, Yangchun; Yao, Junhu (Frontiers in Microbiology, 2021)
Dietary carbohydrates are regarded as the major sources of energy for both ruminants and their microorganism in digestive tract. However, high starch diets have been proven to increase the risk of hindgut acidosis in high-yielding dairy cows. Rumen degradable starch (RDS) can be used as an effective measurement of dietary carbohydrate for ruminant digestive health. Previous studies in ruminants have suggested that dietary carbohydrates can regulate microbial composition and metabolites by alerting the nutrient composition arrived in intestine. Study on the effect of different RDS diets on intestinal bacteria function is helpful to understand the mechanisms between gastrointestinal tract (GIT) microbiota and carbohydrate metabolism in ruminants. A total of 18 lactating goats (45.8 ± 1.54 kg) were randomly divided equally into three dietary treatments with different RDS levels for 5 weeks feeding study: LRDS diet (Low RDS = 20.52%), MRDS diet (Medium RDS = 22.15%), and HRDS diet (High RDS = 24.88%). Compared with LRDS and MRDS groups, HRDS increased cellulose content and acetate proportion in hindgut. The abundance of acetogenic bacteria Ruminococcaceae and Ruminococcaceae UCG-010 were significantly increased in HRDS group. The butyrate proportion and the abundance of butyrate producer Bacteroidale_S24-7, Lachnospiraceae and Bacteroidale_S24-7_group were significantly increased in LRDS group. In addition, LRDS group significantly increased microbial oxidative stress tolerant and decreased potentially pathogenic compared with HRDS group. A metagenomic study revealed that dietary RDS could affect carbohydrate metabolism by increasing glycoside hydrolase 95 (GH95) family and cellulase enzyme (EC 3.2.1.4) in HRDS group; increasing GH13_20 family and isoamylase enzyme (EC 3.2.1.68) in LRDS group. PROBIO database showed the abundance of probiotics significantly decreased in HRDS group. Furthermore, interleukin-1β and secretory immunoglobulin A were up-regulated in hindgut mucosa of HRDS group with decreased expression of Muc2. Dietary RDS level altered the degradation position of carbohydrate and downgraded the cecal gene abundance of cellulolytic enzymes in dairy goats. HRDS diet could become a burden to the intestinal microflora of goat and cause damage to their intestinal mucus layer and inflammation.